Projects of the Japan-Sweden International Balloon and Rocket Experiments in the Arctic Region (g. Future Plan) (Proceedings of the Second Symposium on Coordinated Observations of the Ionosphere and the Magnetosphere in the Polar Regions : Part II) - Tetsuo KAMATA; Seiji ISHIKAWA; Masahiro KODAMA; Tomizo ITOH; Hiroshi FUKUNISHI (National Institute of Polar Research, 1980)
In order to investigate problems of coupling between the middle atmosphere and the ionosphere, and also between the ionosphere and the magnetosphere, it is very important to carry out comprehensive observations of waves, partides, electric field and magnetic field in a high latitude region by a ground-based station, a balloon, a rocket and a satellite. For that purpose, the observation by the international cooperation between Japan and Sweden is planned in the Arctic region. Esrange (67°53'N, 21°O4E) in Sweden is chosen as the observation place, because it is ideally situated for observing various phenomena caused by charged particles coming from space to enter the atmosphere. In this paper, the comprehensive observation plan is described.